2018
DOI: 10.1021/jacs.8b09329
|View full text |Cite
|
Sign up to set email alerts
|

Identification of G-Quadruplex-Binding Protein from the Exploration of RGG Motif/G-Quadruplex Interactions

Abstract: The arginine/glycine-rich region termed the RGG domain is usually found in G-quadruplex (G4)-binding proteins and is important in G4–protein interactions. Studies on the binding mechanism of RGG domains found that small segments (RGG motif) inside the domain contribute greatly to the G4 binding affinity. However, unlike the entire RGG domains that have been broadly explored, the role of the RGG motif remains obscure, with very limited study. Herein, to clarify the role of the RGG motif in G4–protein interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 49 publications
(92 reference statements)
4
86
0
Order By: Relevance
“…The last protein found was TRA2A in nucleotide position 3,056–3,065 and position 3,074–3,083, in both cases with one mismatch (the motifs found were GAAGAAGAAG and the experimentally validated motif for TRA2A is GAAGAGGAAG). All three of these proteins share multiple RGG-rich novel interesting quadruplex interaction (NIQI) motifs, which are common to most human G-quadruplex-binding proteins (Brázda et al, 2018 ; Huang et al, 2018 ; Masuzawa and Oyoshi, 2020 ). All find individual motif occurrence (FIMO) hits below p = 1.10 −4 are enclosed in Supplementary Material 9 .…”
Section: Resultsmentioning
confidence: 99%
“…The last protein found was TRA2A in nucleotide position 3,056–3,065 and position 3,074–3,083, in both cases with one mismatch (the motifs found were GAAGAAGAAG and the experimentally validated motif for TRA2A is GAAGAGGAAG). All three of these proteins share multiple RGG-rich novel interesting quadruplex interaction (NIQI) motifs, which are common to most human G-quadruplex-binding proteins (Brázda et al, 2018 ; Huang et al, 2018 ; Masuzawa and Oyoshi, 2020 ). All find individual motif occurrence (FIMO) hits below p = 1.10 −4 are enclosed in Supplementary Material 9 .…”
Section: Resultsmentioning
confidence: 99%
“…To address this, we first studied the binding of D- hTERC rG4 with nucleolin, and found that the D- hTERC –nucleolin complex band appeared at 20 nM and saturated at 160 nM nucleolin ( Supplementary Figure S16 ), indicating that they indeed directly interacted with each other. Motivated by this novel finding, we further investigated the potential of hTERC rG4 binding with the GAR domain of nucleolin, as GAR domain was commonly identified in G4 binding proteins ( 55 ). Our results suggested that the binding of GAR domain with D- hTERC rG4 to be strong, with K d value of 53.0 ± 13.7 nM (using two-state binding mode).…”
Section: Resultsmentioning
confidence: 99%
“…The identification of G4 associated proteins has mostly relied on affinity proteomics experiments employing RNA and DNA G4 oligomers as baits to isolate G4 interactors from cellular extracts [62][63][64][65]. Other approaches involve computational analysis of genomic protein binding sites to assess the enrichment of predicted G4 motifs within these binding sites [54,66], or meta-analysis, in which shared structural features of G4-binding protein domains were compared to predict new putative G4 interactors [67,68]. In a recent study, a series of protein affinity pull-downs from nuclear lysates with oligonucleotide baits at different concentrations was combined with isobaric tandem-mass-tag labelling and mass spectrometry.…”
Section: Natural G4-binding Proteinsmentioning
confidence: 99%